(untitled) (Gaceta Técnica, 2022)
Several studies on the analysis of the bearing capacity of foundations have been based on the 1920 work of Professor Ludwig Prandtl entitled “Über die härte plastischer körper” (On the hardness of plastic bodies). However, it is not common to find references that present the different considerations behind original proposal. For example, that the proposed method is of theoretical origin, without empirical validation, and that it was not formulated for soils or foundations, since its objective was to evaluate the hardness of a solid material, by determining the stress that produces its total plastification. Considering the above, a rigorous version of the complete original article by Prandtl from 1920 is presented, adapted from German to Spanish. With that, it is expected to contribute to the knowledge about the principles and limits of validity, of the widely known Prandtl-Wedge, which represents one of the pillars of the methods for the geotechnical design of shallow foundations.